Հենրի Լոնգֆելլոյի «Հայավաթի երգը»` Խ. Դաշտենցի թարգմանությամբ - Բաղդասարյան, Ս. Ս.
В статье раскрывается особое отношение Генри Лонгфелло к армянскому песенному искусству,что и стало стимулом для того,чтобы переводчик Хачик Даштенц принялся за перевод прекрасной поэмы "Песнь о Гайавате". Перевод довольно удачный, а сама поэма-воспевание мирного и честного труда. The article expresses Henry Longfellow`s special attitude to armenian song art, that stimulated the translater Khachik Dashtents to translate a wonderful poem “The song of Hiawatha”. The translation is quite good, the poem itself – is the praise of peaceful and honest labour.
Keywords: Գրականագիտություն